Injury mortality indicators: recommendations from the International Collaborative Effort on Injury Statistics. Issue 4 (14th June 2011) - Cryer, Colin; Fingerhut, Lois; Segui-Gomez, Maria
Abstract : Background: The International Collaborative Effort (ICE) on Injury Statistics called for an effort 'to reach consensus on what are the 10 most important indicators of injury incidence that offer the potential for international comparisons and for regional or global monitoring.' Objectives: To describe the process of developing the ICE indicators and to present the specifications of selected injury mortality indicators, along with comparisons between selected countries for those specified indicators. Methods: Participants on the ICE list had been asked to send to one of the authors what they considered the most important five indicators of injury incidence. These were synthesised and presented under six themes: mortality indicators (general); mortality indicators (motor vehicle); mortality indicators (other); hospital data-based (overall); hospital data-based (traumatic brain injury (TBI)); long-term disability (overall). Following two work group discussions and after drafting and revising indicator specifications, agreement was reached on mortality indicators and specifications. Specifications for those mortality indicators are presented. Morbidity indicators are still to be agreed. Results: The mortality indicators proposed were age-adjusted rates of injury death; motor vehicle traffic crash-related death; self-harm/suicide; assault/homicide; and TBI death. The empirical work highlighted difficulties in identifying TBI in countries whe re mortality data do not capture multiple injuries, prompting us to drop the mortality indicator related to TBI and moving us instead to introduce an indicator to monitor the use of undetermined intent in the classification of injury mortality. Conclusion: The ICE has reached a consensus on what injury mortality indicators should be used for comparison between countries. Specifications for each of these have been applied successfully to the mortality data of seven countries.